SERANGGA PERMUKAAN TANAH PADANG RUMPUT KAWASAN DANAU LAUT TAWAR KABUPATEN ACEH TENGAH - Aryediatami Naura Kamila Manik; Ade Niar; Jihan Nabila; Elita Agustina; Zuraidah Zuraidah (Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia., 2022)
Central Aceh district includes the central part of Sumatra Island which is part of the Bukit Barisan mountains, with the capital in Takengon with lowlands, and the central part of the area is partly hills. One of the communities found in the grasslands of the freshwater lake area of Waq Toweren Village are ground surface insects. This research was conducted in Waq Toweren Village, Lut Tawar District, Central Aceh Regency, on March 25, 2022. The method used was purposive sampling with data collection using pitfall traps as many as 14 plots installed in the morning (06.00-18.00) and afternoon. (18.30-06.00). The results showed that the genus most commonly found was the genus Aphaenogaster. The least found genera are Grilode, Trechus, Musca, Selonopsis, Evania, Periplaneta, Hydrophilidae, Drosophila, Monolepta.Keywords: Ground surface insects, freshwater lake area